2020
DOI: 10.18203/2394-6040.ijcmph20202483
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment lost to follow up among presumptive tuberculosis patients in a tertiary care centre, South India

Abstract: Background: At tertiary care centres, presumptive tuberculosis (TB) patients who come from far off places and are more likely to drop out during diagnosis or before treatment initiation. We aimed to describe the proportion lost during diagnosis or before treatment and also assessed the reasons for the loss to follow up.Methods: We did a hospital based descriptive study, reviewing laboratory register and referral register to assess the status of submission of second sputum and referral letter, respectively, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A previous study done in the same setting had shown that only two thirds of the diagnosed TB patients are referred for treatment initiation, and there was a substantial delay between the diagnosis and the referral. [ 26 ] Although the mobile call reminders reduced the delay between the patient referral and the treatment initiation, there was no significant reduction in the overall delay between diagnosis and treatment initiation. This is rightly so, as the mobile voice call reminders were given only after referring the patient for treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study done in the same setting had shown that only two thirds of the diagnosed TB patients are referred for treatment initiation, and there was a substantial delay between the diagnosis and the referral. [ 26 ] Although the mobile call reminders reduced the delay between the patient referral and the treatment initiation, there was no significant reduction in the overall delay between diagnosis and treatment initiation. This is rightly so, as the mobile voice call reminders were given only after referring the patient for treatment initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In low and middle-income countries like Ethiopia, pretreatment loss to follow-up ranges from 4% to 38%. [6][7][8][9] Moreover, 30% of patients with presumptive TB are lost during the diagnosis process. 10 Passive case-finding is the main approach currently applied by most national TB control programmes, including Ethiopia.…”
Section: Introductionmentioning
confidence: 99%